TINJAUAN GREEN ACCOUNTING, KINERJA LINGKUNGAN, CORPORATE SOCIAL RESPONSIBILITY, BIAYA LINGKUNGAN DAN KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR - Dina Salsabila Oktaviana Dinistri; Agus Khazin Fauzi; Ni Nyoman Yuliati (Jurnal Riset Akuntansi, 2024)
This research aims to test and analyze the influence of green accounting, environmental performance, corporate social responsibility and environmental costs on the financial performance of manufacturing companies. Annual report data for the 2019-2023 period and PROPER documents are used in this research which are accessed on the pages www.idx.co.id and https://proper.menlhk.go.id. Purposive sampling technique was used to select a sample of companies where the number of samples obtained was 20 companies with a 5 year observation period, resulting in 100 observation data. Data analysis in this study used e-views software version 12. The results of the study found that the green accounting and environmental costs variables did not have a significant effect on financial performance, while the CSR variables and environmental performance had a significant effect on financial performance.